The maritime cultural landscape of the Ria de Aveiro lagoon (Portugal) in the Early Modern period - Carvalho, Patrícia Catarina Sanches de (2018)
UID/HIS/04666/2013 SFRH/BD/68443/2010 SFRH/BD/76416/2011